1995
DOI: 10.1155/1995/69454
|View full text |Cite|
|
Sign up to set email alerts
|

Hemopoiesis in the Thymus

Abstract: The presence in the thymus of hemopoietic cells other than thymocytes has been known for many years, but the extent of the hemopoietic activity of the thymus and the possible functional implications have only recently begun to receive much attention. This review summarizes the literature in this field, especially in the light of current cytokine and thymic-factor knowledge, and includes clinical relevance where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…CCX-CKR1 expression is restricted to TECs ensheathing the blood vessels of the medulla, the corticomedullary junction, and to subcapsular zone TECs. This expression pattern overlaps but is not identical with the location of type I epithelium that has been classified on the basis of ultrastructural analyses (30)(31)(32), because type I epithelial cells ensheathing cortical blood vessels are CCX-CKR1-negative. CCX-CKR1 marks the thymic niche to which hematopoietic precursors are recruited from the blood.…”
Section: Discussionmentioning
confidence: 84%
“…CCX-CKR1 expression is restricted to TECs ensheathing the blood vessels of the medulla, the corticomedullary junction, and to subcapsular zone TECs. This expression pattern overlaps but is not identical with the location of type I epithelium that has been classified on the basis of ultrastructural analyses (30)(31)(32), because type I epithelial cells ensheathing cortical blood vessels are CCX-CKR1-negative. CCX-CKR1 marks the thymic niche to which hematopoietic precursors are recruited from the blood.…”
Section: Discussionmentioning
confidence: 84%
“…suppression of red blood cell production or blood loss), typically peaks at 4-7 days, and gradually declines within 2-3 weeks of the original insult (Fernandez and Grindem, 2006). To our knowledge, our study is the first to examine changes in proportion of reticulocytes across the reproductive cycle, although previous studies have investigated changes in the hematopoietic organs in this context (reviewed by Kendall, 1995;Kalmbach et al, 2004). For example, Jones (Jones, 1983) documented that the thymus became enlarged and actively produced red blood cells in the redbilled quelea (Quelea quelea) during incubation, and suggested that this functioned to augment erythropoiesis in the bone marrow and compensate for anemia during egg-laying.…”
Section: Discussionmentioning
confidence: 95%
“…A variable amount of intrathymic MCs has been reported during embryogenesis in different species (Bodey et al 1998). This finding has not stimulated any interpretative effort, being merely considered a secondary phenomenon related to a certain degree of hematopoiesis that occurs in this organ in the early stages of development (Kendall 1995;Kendall et al 1999). However, the high number of MCs observed in the chick embryo thymus-coupled with the ultrastructural features of MC degranulation and the close relationship between MCs and the extracellular matrixdeserves special attention and suggests some possible, still unknown, MC functions during thymic organogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic studies have reported on MC localization to embryonic thymus, and data have been related to a certain degree of hematopoiesis that occurs in this organ during embryogenesis (Bodey et al 1998;Kendall 1995;Kendall et al 1999). In the present study, we investigated by transmission electron microscopy the rich population of MCs in the chicken thymus during embryonic life.…”
Section: Introductionmentioning
confidence: 99%